Targeting TMEM205 mediated drug resistance in ovarian clear cell carcinoma using oncolytic virus - Uksha Saini; Brentley Q. Smith; Kalpana Deepa Priya Dorayappan; Ji Young Yoo; G. Larry Maxwell; Balveen Kaur; Ikuo Konishi; David O'Malley; David E. Cohn; Karuppaiyah Selvendiran (BMC, 2022)
Abstract Background Ovarian clear cell carcinoma (OCCC) accounts for approximately 8-10% of epithelial ovarian cancers in the United States. Although it is rare, OCCC usually presents with treatment challenges and the overall prognosis is far worse than high grade serous ovarian cancer HGSOC. The objective of this study was to examine the therapeutic relevance of combining oncolytic virus with cisplatin for ovarian cancer clear cell carcinoma (OCCC). Results We identified that TMEM205, a recently discovered transmembrane protein, contributes to chemoresistance in OCCC cells via the exosomal pathway. Mechanistically, TMEM205 undergoes ligand-independent constitutive endocytosis and co-localizes with Rab11 to contribute to the late recycling endosomes in a clathrin-independent manner. Further, we observed that oncolytic virus (oHSV) pretreatment followed by treatment with cisplatin decreases TMEM205 expression and sensitizes cells to cisplatin in a synergistic manner in OCCC cells. TMEM205 interacts with glycoprotein-C of oHSV post-infection; both of these proteins undergo ubiquitination and ultimately get shuttled outside the cell via exosomes. Thus, we demonstrate the mechanotransduction pathway of TMEM205-mediated chemoresistance along with targeting this pathway using oHSV and cisplatin as a powerful therapeutic strategy for OCCC. oHSV combination with cisplatin inhibits OCCC tumor growth in vivo in immunodeficient and immunocompetent mice models. Conclusion Our results suggest that the combination of oHSV and cisplatin in immunocompetent as well as immune deficient OCCC tumor bearing mice reduces overall tumor burden as well as metastatic disease thereby providing survival benefit. Additionally, the detection of TMEM205 in exosomal cargo early in OCCC development has potential to be exploited as a biomarker.